Design and Implementation of a Blockchain-Enabled Cloud Architecture for Accelerated User Transactions - Kumar, V Uday; Chatrapati, Kaila Shahu (South Eastern European Journal of Public Health, 2025)
Over the years, Centralized Systems are servicing billions of people all around the world. Most of the today’s popular applications like Facebook, Twitter, Instagram, Amazon, Google etc. are based on centralized systems. There are few disadvantages of centralized systems. The first disadvantage is that if the central system fails, the entire system may become inaccessible, leading to complete downtime. The second disadvantage is as the system grows, the central node can become a bottleneck, struggling to handle increased loads efficiently. This can lead to delays and degraded performance. The third one is about security. If someone hacks central system, the entire customers data may be compromised. Unlike centralized systems, Blockchain allows to distribute data among all nodes preventing single point failure. Since the data is distributed and each blocks have their own hash key linked with other, its merely impossible to tamper a transaction. Blockchain can be easily scalable when compared to centralized systems. In this paper, we design and implement BAF (Blockchain Architecture for Fast execution of transactions). We select only fewer number of users ledger to update the transactions. Multithreading is used to perform write operation on selected ledgers. The experimental results showed that proposed work reduced 28% of execution time of user transactions at an average case.